What is an emotional disorder? A transdiagnostic mechanistic definition with implications for assessment, treatment, and prevention. Issue 2 (14th March 2019) - Bullis, Jacqueline R.; Boettcher, Hannah; Sauer‐Zavala, Shannon; Farchione, Todd J.; Barlow, David H.
Abstract: We present a transdiagnostic definition of the commonly used, but poorly defined, term emotional disorder . This definition transcends and possibly complements traditional descriptive diagnostic categories, and candidate dimensional models of psychopathology by focusing on putative mechanisms that contribute to the onset and maintenance of disorders characterized primarily by dysfunction in the interpretation and regulation of emotion. We review three intermediate transdiagnostic mechanisms that characterize emotional disorders, such as, but not limited to, anxiety and depressive disorders, and then illustrate how this proposed definition applies to additional diagnoses beyond anxiety and depression. Implications of this new conceptualization of disorders of emotion are then discussed in the context of assessment, treatment, and prevention.